Comercialization of Airnav Indonesia as Air Navigation Provider: Is it beneficial? - Wirsamulia, Feri (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2020)
The aim of the research is to analyse whether commercialization air navigation service and how Airnav Indonesia as a provider may have a benefit from it. This normative legal research uses statutory approach. The results of research show that following the transfer of authority and responsibility from PT. Angkasa Pura I and PT. Angkasa Pura II as the air navigation service provider in January 2013, the air navigation service in Indonesia entered into a new chapter which is monopolized by one company, that is â€œLembaga Penyelenggara Pelayanan Navigasi Penerbangan Indonesiaâ€ (LPPNPI) or â€œAirnav Indonesiaâ€. By the Governmental Decree No. 77 of 2012, Airnav Indonesia was established to provide air navigation service in order to secure the aviation safety and air traffic over the Indonesia territory. Generally, air navigation service is treated as public service in many countries, however, the idea to commercialize the air navigation service has been applied in some countries. The Government should consider altering Airnav Indonesia from a public service company to be a commercial business company which may contribute to the Governmentâ€™s income. Commercialization of the air navigation service will provide a mutual benefit not only among stakeholders in the aviation industry, but also for aviation safety. Eventually, the Airnav Indonesia as the sole air navigation service provider in Indonesia could be a profit centre institution instead of merely a public service company.